Immune priming and experimental glaucoma: the effect of prior systemic lipopolysaccharide challenge on tissue outcomes after optic nerve injury. (23rd January 2014) - Narayan, Daniel S; Casson, Robert J; Ebneter, Andreas; Chidlow, Glyn; Grace, Peter M; Hutchinson, Mark R; Wood, John PM
Abstract Background Microglial activation is a prominent feature throughout the optic pathway in experimental glaucoma. Pro‐inflammatory microglial activation may contribute to neurodegeneration through the release of pro‐inflammatory cytokines and other inflammatory mediators. Systemic administration of lipopolysaccharide stimulates microglia to produce pro‐inflammatory cytokines and chemoattractants. A preliminary investigation demonstrated pro‐inflammatory microglial activation throughout the optic pathway following systemic lipopolysaccharide challenge. The aim of the current work was to investigate whether microglial priming with lipopolysaccharide would exacerbate optic nerve injury in rats following experimental glaucoma. Methods Adult female Sprague‐Dawley rats were divided into lipopolysaccharide treatment (n = 15) and saline treatment groups (n = 15). Microglial priming was induced with a 2.5‐mg/kg intraperitoneal injection of lipopolysaccharide; control animals received saline. Experimental glaucoma was induced 48 h later in the right eyes of animals by laser photocoagulation of the trabecular meshwork. Animals were sacrificed 9 days after laser treatment. Results The estimated number of axons per optic nerve was 51 327 ± 3868 (mean ± standard error of the mean) in the lipopolysaccharide group and 54 569 ± 6687 (mean ± standard error of the mean) in the saline group. Optic nerve axon counts were not significantly different between lipopolysaccharide and saline groups (P = 0.67). Conclusions Systemic lipopolysaccharide challenge had no discernible effect on optic nerve injury in laser‐induced experimental glaucoma. These findings do not support the hypothesis that this model of experimental glaucoma involves inflammation and instead suggest that microglial activation may occur secondary to chronic neurodegeneration.